2006
DOI: 10.1080/09712119.2006.9706589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium-Vitamin E or Progestagen-PMSG Injections on Reproductive Performance of Ewes

Abstract: InjectionsKoyuncu, M., Kara Uzun, $., Oz+, $.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, in this trial, injection of Se plus vitamin E did not increase the reproduction and production performance in younger ewes (Gabryszuk & Klewiec, 2002). Positive effects of Se or Se-vitamin E on fertility were observed by other authors (Scales, 1974;Mihajlovic et al, 1991;Koyuncu et al, 2006), but not confirmed (Segerson et al, 1986). A permeating dose of 5 mg selenium reduced the numbers of barren Merino ewes by 15% (Scales, 1974).…”
mentioning
confidence: 68%
“…However, in this trial, injection of Se plus vitamin E did not increase the reproduction and production performance in younger ewes (Gabryszuk & Klewiec, 2002). Positive effects of Se or Se-vitamin E on fertility were observed by other authors (Scales, 1974;Mihajlovic et al, 1991;Koyuncu et al, 2006), but not confirmed (Segerson et al, 1986). A permeating dose of 5 mg selenium reduced the numbers of barren Merino ewes by 15% (Scales, 1974).…”
mentioning
confidence: 68%
“…The birth weight, daily weight gain, fleece yield, breeding age and litter size were 4.4 kg, 322 g, 3.6 kg, 10-14 months and 1.4 in the Merino, respectively (TAGEM, 2011). Some research has been performed on the hormonal application of the reproductive cycle of the Merino sheep, particularly oestrus synchronisation (Koyuncu et al, 2006). Among breeds, the Merino is considered to have low prolificacy.…”
Section: Introductionmentioning
confidence: 99%